The Acari Hypothesis, IV: revisiting the role of hygiene in allergy - Retzinger, Andrew C.; Retzinger, Gregory S. (Frontiers in Allergy, 2024)
Allergy and its manifestations were first appreciated in the 1870 s. Today, the mechanism by which specific substances elicit allergic reactions remains poorly understood. This is problematic from a healthcare perspective because the prevalence of allergic disease and its societal costs are substantial. Regarding mechanistic understanding of allergy, a new proposal, The Acari Hypothesis, has been forwarded. The Hypothesis, borne from consideration of alpha-gal syndrome, postulates that acarians, i.e., mites and ticks, are operative agents of allergy. By way of their pathogenic payloads and salivary pattern recognition receptor(s), acarians potentiate in human hosts the generation of IgE against acarian dietary elements. Those elements account for most, if not all, known human allergens. Inasmuch as acarian—human interactions occur on human epithelial surfaces, it is to be expected factors that influence the presence and/or operation of acarians on those surfaces influence the expression of allergic diseases. In this report, it is proposed that two adaptations of catarrhine primates, i.e., Old World monkeys, apes and humans, evolved to deter acarian species: firstly, the expansion of eccrine glands across the entirety of body surface area, and, secondly, the secretion of sweat by those glands. Contemporary hygienic practices that reduce and/or disrupt the operation of eccrine glands are likely responsible for the increase in allergic disease seen today.